The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1136/jnnp.74.7.933
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction in young men following head injury in childhood and adolescence: a population study

Abstract: Objectives: To examine the prevalence of cognitive dysfunction among young men who had suffered a head injury during childhood or adolescence, in particular focusing upon the effects of age and the severity of the injury. Methods: By cross linkage of Danish national registers for hospital admissions and the draft board, 3091 young men were identified who had been injured before age 18 and tested at age 18 or shortly thereafter: 970 had suffered a single concussion and were in hospital for one day only; 521 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 26 publications
(25 reference statements)
1
28
0
Order By: Relevance
“…A recent study among professional football players found no association of time between repeat concussions and number of reported postconcussive symptoms [21]. Another study found similar results, though time between events was analyzed as a dichotomous variable of less than or greater than 6 months, which may have diluted any association [27]. One recent study found evidence of a mediating effect of time, but this study used electroencephalography to directly measure brain function [14].…”
Section: Time Between Eventssupporting
confidence: 48%
“…A recent study among professional football players found no association of time between repeat concussions and number of reported postconcussive symptoms [21]. Another study found similar results, though time between events was analyzed as a dichotomous variable of less than or greater than 6 months, which may have diluted any association [27]. One recent study found evidence of a mediating effect of time, but this study used electroencephalography to directly measure brain function [14].…”
Section: Time Between Eventssupporting
confidence: 48%
“…A longitudinal study in Denmark followed a birth cohort of young men to look at the effect of age at injury, and severity of injury, on a draft board"s compulsory cognitive functioning test, taken at the age of eighteen years [16]. The results suggested that a single head injury after eleven years of age, not requiring admission to hospital for more than one day, was linked with higher failure rate in the cognitive test when compared to the non-injured cohort.…”
Section: 3a Childhood Head Injurymentioning
confidence: 99%
“…It is widely recognised that a proportion of "minor" head injury patients will continue to suffer disability and symptoms beyond six months after their injury [11,16,51,87,88], whereas most physiological effects would be expected to have subsided within three months [67,83].…”
Section: Physiology Vs Psychologymentioning
confidence: 99%
“…It has been proved that adolescents and adults recover neurological functions after sever TBIs with equal effectiveness [34]. Other scientists assume that adolescents are capable of a relatively fast recovery of motor and sensory functions even after severe TBI (just like children) [39]. Other neurological disorders commonly include speech and sight impairment and sleep disorders [17,19,21].…”
mentioning
confidence: 99%
“…According to the ICD-10, cognitive disorders after TBIs are classified in the framework of post-concussional syndrome (F07.2). There are three levels of post-traumatic cognitive disorders [14,16,39]: 1) traumatic encephalasthenia (dynamic functional disorders);…”
mentioning
confidence: 99%